Removal Of Pharmaceutically Active Compounds In Environmental Waters Using Polymer Inclusion Membranes - Olasupo, Ayo (2022)
The presence of residues of pharmaceutically active compounds in aquatic environments is a daunting issue of great concern. The occurrence, fate and potential toxicity of these contaminants in different environmental media have triggered the interest of the science community. They have been found in varying concentrations from ng/L to mg/L in different environmental matrices. As a result of their high solubility and low volatility, they are often found in the aquatic environment and the wastewater treatment plants (WWTPs) are their major reservoir. However, conventional WWTPs are incapable of removing these contaminants completely during treatments; hence, there is a need to explore other advanced wastewater treatments to compensate for the lapses of conventional WWTPs. In this study, an investigation on the removal of recalcitrant contaminants such as ciprofloxacin (CIP), sulfamethoxazole (SMZ), and diclofenac (DCF) from wastewater using polymer inclusion membranes (PIMs) fabricated from different base polymers (polyvinyl chloride (PVC) and cellulose triacetate (CTA), different carriers (bis-2-(ethylhexyl) phosphate (B2EHP) and tricapryl-methylammonium chloride (Aliquat 336)), and different plasticizers (dioctyl phthalate (DOP) and 2-nitro phenyl ether (NPOE)).